1996
DOI: 10.1046/j.1365-2958.1996.5571084.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus fumigatus chsC and chsG genes encode Class III chitin synthases with different functions

Abstract: Two genes, designated chsC and chsG were isolated from DNA libraries of the opportunistic fungal pathogen, Aspergillus fumigatus. The genes were characterized with respect to their nucleotide sequences and mutant phenotypes. The complete deduced amino acid sequences of chsC and chsG show that the products of both genes are Class III zymogen-type enzymes. A mutant strain constructed by disruption of chsC is phenotypically indistinguishable from the wild-type strain, but chsG- and chsC- chsG- strains have reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
107
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 36 publications
6
107
1
1
Order By: Relevance
“…The chitin content of deficient mutants was found to be reduced only in Dchs1 and Dchs2, with a 10 % reduction in comparison to wild-type strain 4287 (Table 1). It has been previously described in A. fumigatus that only mutants defective in class III CS or homologues of this protein have a significant reduction in chitin content (Din et al, 1996), while mutants defective in the zymogen type of enzyme typically have a normal or a small reduction (10 %) in chitin content and CS activity (Mellado et al, 1996a).Pathotypic behaviour of Dchs1, Dchs2 and Dchs7 mutant strainsTo determine the effect of chs mutations on virulence of F. oxysporum, root infection assays with tomato plants were performed. Two-week-old plants were inoculated by immersing their roots in a microconidial suspension of the wild-type strain, or the disruptants Dchs1, Dchs2 and Dchs7.…”
mentioning
confidence: 99%
“…The chitin content of deficient mutants was found to be reduced only in Dchs1 and Dchs2, with a 10 % reduction in comparison to wild-type strain 4287 (Table 1). It has been previously described in A. fumigatus that only mutants defective in class III CS or homologues of this protein have a significant reduction in chitin content (Din et al, 1996), while mutants defective in the zymogen type of enzyme typically have a normal or a small reduction (10 %) in chitin content and CS activity (Mellado et al, 1996a).Pathotypic behaviour of Dchs1, Dchs2 and Dchs7 mutant strainsTo determine the effect of chs mutations on virulence of F. oxysporum, root infection assays with tomato plants were performed. Two-week-old plants were inoculated by immersing their roots in a microconidial suspension of the wild-type strain, or the disruptants Dchs1, Dchs2 and Dchs7.…”
mentioning
confidence: 99%
“…More meaningful comparisons should be possible after complete Phycomyces genes have been cloned. In our hands, the amplification procedure failed to reveal sequences that match class III, which was detected in filamentous ascomycete fungi such as Aspergillus species (Mellado et al, 1995(Mellado et al, , 1996Yanai et al, 1994) and Neurospora crassa (Yarden and Yanofsky, 1991). Functional analysis using gene disruptions Mellado et al, 1996;Yanai et al, 1994;Yarden and Yanofsky, 1991) has indicated the potential role played by class III-CHS in hyphal growth in fungi.…”
Section: Discussionmentioning
confidence: 82%
“…An attractive possibility is that each gene or a combination of certain genes is temporally and spatially regulated in cell wall synthesis during cell growth and differentiation. In fact, functional analysis using gene disruptants has shown that certain CHS genes that are responsible for cell morphology in Aspergillus nidulans Motoyama et al, 1997;Specht et al, 1996;Yanai et al, 1994) and Aspergillus fumigatus (Mellado et al, 1996) indicate highly specialized expression patterns. In the zygomycete fungus P. blakesleeanus, although a CHS gene was identified, only a PCR product amplified from that gene was actually cloned; it belongs to class II-CHS (Miyazaki et al, 1993).…”
mentioning
confidence: 99%
“…In Saccharomyces cerevisiae, chitin synthesis requires three chs genes coding for three distinct enzymes with a specific role at different stages of the life cycle (Bulawa, 1993). Filamentous fungi generally possess a higher number of chs genes (Mellado et al, 1996 ;Specht et al, 1996). This has been correlated with their more complex developmental events and the increased chitin content in their cell walls .…”
Section: mentioning
confidence: 99%